The Effect Of Kaizen Culture And Work Discipline On Employee Performance At Klambir V Kebun Village Office - Siswa Pratama; Ahmad Fadlan; Maudy Lestari (MANAGER: Journal of Management and Administration Science, 2024)
Employees are the main wealth of a company or organization, because their participation is the key to the running of an organization activities. In every successful organization or corporation, it must have qualified employees, so it is important for organizations to be able to optimize their employees in accordance with their functions in order to become quality and superior assets whose realization can be seen through employee achievement or performance. Additionally, cultivating an organizational culture that supports these workers' performance is one strategy to generate human resources with good human resources with good performance in order to fulfill the work unit's vision and objective. This research was aimed to determine how Kaizen culture and work discipline related to employee performance. This kind of research employed a quantitative descriptive technique. There were 30 respondents for this study, who were chosen through nonprobability sampling with purposive sampling technique.  The data collection method used observation and questionnaire. The data were analyzed using SPSS version 25. The research results revealed that Kaizen culture partially affected employee performance in Klambir V Kebun village. Work discipline partially affected employee performance in Klambir V Kebun village. Finally, Kaizen culture and work discipline simultaneously affected employee performance in Klambir V Kebun village.